SOLID PHASE MICROEXTRACTION (SMPE) VOLATILE COMPOUNDS OF GENUS Origanum - Huamán Castilla, Nils (2016)
This research aims to identify the volatile compounds of genus Origanum. For this purpose 50 samples was collected locations: Porobaya, San June, Otora, Doce Quebradas and Tala; belonging at district of Torata-Moquegua; Samples collected were characterized taxonomically finding four species Origanum majoricum (compact and loosely), Origanum majorana and Origanum plegatifolium. Subsequently the volatiles were analyzed by solid phase microextraction (SMPE) and GC-MS. 31 compounds were identified by comparison with literature, co-elution with standard and comparing retention indices, finding that the content of thymol and carvacrol range from 7 to 14 mg/g and 37 to 49 mg/g respectively. Porobaya samples and San June are increasing the amount of thymol present; Otora samples being more carvacrol content. Therefore the SMPE turns out to be a quick and easy method for identifying volatile aromatic plants.